PERAN KOMPETENSI, BUDAYA ORGANISASI DAN WORK LIFE BALANCE TERHADAP MOTIVASI KERJA PADA PT.BPR BANK BULELENG 45 (PERSERODA) - Ryan Purwa Adi Pratama, I Putu; Ayu Permoni, Ni Luh Eka (Jurnal Daya Saing, 2025)
This study aims to analyze the influence of competence, organizational culture, and work life balance on work motivation among employees at PT. BPR Bank Buleleng 45 (Perseroda). The background of this research is based on the fact that the target for optimal credit distribution realization has not yet been achieved, despite various strategies having been implemented, indicating low employee work motivation. Data were collected through questionnaires distributed to 30 employees and analyzed using the Structural Equation Modeling Partial Least Square (SEM-PLS) method. The results of the study show that both organizational culture and competence have a positive and significant effect on work motivation, whereas work life balance has a negative but significant effect. A conducive organizational culture and high employee competence can increase work motivation, while poor management of work-life balance can reduce work enthusiasm. This research emphasizes the importance of creating a supportive work environment and improving human resource quality to support the achievement of company targets. The findings are expected to serve as a consideration in the formulation of human resource management policies in the banking sector, especially at BPR.